2017
DOI: 10.1615/intjmedmushrooms.v19.i5.50
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition of Some Cultivated and Wild Culinary-Medicinal Mushrooms from Hungary

Abstract: The volatile constituents of the fruiting bodies of 4 culinary-medicinal mushroom species (Agaricus bisporus, Boletus edulis, Cantharellus cibarius, and Hericium erinaceus) from Hungary were examined to review their aroma composition. Simultaneous distillation/extraction was applied to extract volatile compounds from fungi, and the values were measured with gas chromatography--mass spectrometry. Although the fragrances of fungi are not as characteristic as those of spices, several groups of volatile compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It was previously found that 1-octen-3-ol and 3-octanone are secondary metabolites of most mushrooms and give them their typical "mushroom-like" odor [32]. According to Csóka et al, the percentage of the 8-carbon volatiles in cepe was notably high (65.41%), and 1-octen-3-ol was the predominant compound [33]. e high ratio of this "mushroom alcohol" in B. edulis was reported by other authors as well [1,34].…”
Section: Volatile Composition Of Fresh and Dried Cepementioning
confidence: 99%
“…It was previously found that 1-octen-3-ol and 3-octanone are secondary metabolites of most mushrooms and give them their typical "mushroom-like" odor [32]. According to Csóka et al, the percentage of the 8-carbon volatiles in cepe was notably high (65.41%), and 1-octen-3-ol was the predominant compound [33]. e high ratio of this "mushroom alcohol" in B. edulis was reported by other authors as well [1,34].…”
Section: Volatile Composition Of Fresh and Dried Cepementioning
confidence: 99%
“…Some species of Candida and Pichia also have inhibitory activities on A. flavus and its aflatoxins [ 20 ]. In addition, various volatiles from Hericium erinaceus [ 21 ] and plants such as Zingiber officinale [ 22 ], citronella [ 23 ], thyme [ 24 ], and cinnamon [ 25 ] have been reported to be helpful in the management of many pathogens both before and after harvest. Previous research conducted in the last decade has shown that the volatiles from bacteria exert inhibitory activity against various plant pathogens [ 16 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For hundreds of years, mushrooms have been used by humans both to meet their nutritional needs and to treat various diseases (Gaglarirmak, 2011;Gustafson, 2016;Chatterjee et al, 2017). Edible mushrooms are considered among the indispensable elements of diets due to their rich nutritional contents, as well as being delicious enough to be consumed by many people (Csóka et al, 2017;Luo et al, 2017;Sharma & Gautam, 2017;Politowicz et al, 2018). In recent studies, it has been reported that especially phenolic compounds contribute significantly to the biological activities of mushrooms (Sevindik et al, 2020).…”
Section: Introductionmentioning
confidence: 99%